Comprehensive Analyses of circRNA Expression Profiles and Function Prediction in Chicken Cecums After Eimeria tenella Infection - Yu, Hailiang; Mi, Changhao; Wang, Qi; Zou, Wenbin; Dai, Guojun; Zhang, Tao; Zhang, Genxi; Xie, Kaizhou; Wang, Jinyu; Shi, Huiqiang (Frontiers in Cellular and Infection Microbiology, 2021)
Coccidiosis is an important intestinal parasitic disease that causes great economic losses to the global poultry production industry. Circular RNAs (circRNAs) are long non-coding RNAs that play important roles in various infectious diseases and inflammatory responses. However, the expression profiles and functions of circRNAs during Eimeria tenella (E. tenella) infection remain unclear. In this study, high-throughput sequencing was carried out to detect circRNAs in chicken cecal tissues from the control (JC), resistant (JR), and susceptible (JS) groups on day 4.5 postinfection (pi), respectively. A total of 104 circRNAs were differentially expressed, including 47 circRNAs between the JS and JC groups, 38 between the JR and JS groups, and 19 between the JR and JC groups. Functional analyses indicated that these differentially expressed circRNAs were involved in pathways related to E. tenella infection; the adaptive immune response was enriched in the JS vs JC group, the NF-kappa B signaling and natural killer cell-mediated cytotoxicity pathways were enriched in the JS vs JC and JR vs JC groups, while the B cell receptor signaling pathway was enriched in only the JR vs JC group. Moreover, the coexpression network of differentially expressed circRNAs and mRNAs suggested that circRNA2202 and circRNA0759 associated with DTX1 in the JS vs JC group, circRNA4338 associated with VPREB3 and CXCL13L3 in the JR vs JC group, and circRNA2612 associated with IL8L1 and F2RL2 in the JR vs JS group were involved in the immune response upon E. tenella infection. In conclusion, our results provide valuable information on the circRNAs involved in the progression of chicken E. tenella infection and advance our understanding of the circRNA regulatory mechanisms of host resistance and susceptibility to E. tenella infection in chickens.